Fire resistance of ceramic-masonry sealing blocks using intumescent paint protection - Santos Sales, Carlos Alexandre; Gomes do Nascimento, Carlos Fernando; Marques da Silva, Thais; Marques Barreto, Lydia; Casado Lordsleem Júnior, Alberto; de Albuquerque Soares, Willames; Castro Borges, Pedro; Barreto Monteiro, Eliana Cristina (Revista ALCONPAT, 2019)
The efficiency of surface protection of sealing masonry structures with intumescent ink was evaluated in relation to mechanical resistance and thermal insulation. Sixty ceramic sealing masonry blocks were used. The temperature of the face directly exposed to the flame was on average 25% lower for the block with passive protection. The compressive strength of the blocks with passive protection was about 70% higher than the unprotected blocks, after 60 minutes of direct exposure to the flame. More than 70% of the blocks without passive protection and that were exposed to flame had compressive resistance of 1.35 MPa, while 100% of the blocks with protection had values 2.38 MPa, even after 60 minutes of exposure.